The complete fairy tales of Charles Perrault - Perrault, Charles, 1628-1703.; Holmes, Sally (New York : Clarion Books, 1993)
An illustrated collection of eleven tales including such familiar ti tles as "Cinderella" and "Sleeping Beauty" and less familiar ones such as "Tufty Ricky" and "The Fairies."
Includes bibliographical references (p.153-156).
Keywords: Fairy tales -- France; Children's stories, French -- Translations into English; Fairy tales; Folklore -- France